The Effect of Pop Up Book Media in Science Learning: A Literature Review - Nurfitra Yanto; Muliana GH; Sakinah Zubair (EduLine: Journal of Education and Learning Innovation, 2023)
This study aims to analyze the influence of Pop Up Book Media in science learning. This study is a qualitative research in the form of literature studies. The articles reviewed in this study are articles sourced from accredited journals of at least SINTA 4 published in 2023,2022,2021,2020, and 2019. There are 40 articles collected, but only 20 articles are considered relevant to the focus of this study. 20 this article and all articles related to media Pop up Book on learning science or science content. In this study it was found that the use of Creative Learning media such as Pop Up Book media has a positive impact on the learning process. Pop Up Book Media can improve learning outcomes and can train high-level thinking skills in learners. In addition, it was also found that Pop-Up Book media can provide cognitive reinforcement and increase learner motivation. In certain cases it was found that Pop Up Book media can help improve the understanding of students who have limitations related to science content. In this study it was also found that Pop up Book Learning media can be used in various learning models and can support the scientific literacy of learners.